2017
DOI: 10.1038/s41598-017-13504-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretagogues hexarelin and JMV2894 protect skeletal muscle from mitochondrial damages in a rat model of cisplatin-induced cachexia

Abstract: Chemotherapy can cause cachexia, which consists of weight loss associated with muscle atrophy. The exact mechanisms underlying this skeletal muscle toxicity are largely unknown and co-therapies to attenuate chemotherapy-induced side effects are lacking. By using a rat model of cisplatin-induced cachexia, we here characterized the mitochondrial homeostasis in tibialis anterior cachectic muscle and evaluated the potential beneficial effects of the growth hormone secretagogues (GHS) hexarelin and JMV2894 in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 69 publications
2
69
2
Order By: Relevance
“…In animal models of cisplatin-induced cachexia, it has been shown that cisplatin treatment in fast-twitch skeletal muscle stimulated cell autophagy by decreasing the level of active Akt and therefore, phosphorylated FoxO3a, thus favoring its localization in the nucleus. Accordingly, a parallel upregulation of genes coding for autophagy proteins such as Beclin-1, a protein involved in autophagy starting, and LC3-II and p62 has also been observed [36]. A similar effect has been also associated to cisplatin in an in vitro study performed on C2C12 myotubes [37].…”
Section: Autophagy Pathwaymentioning
confidence: 78%
See 4 more Smart Citations
“…In animal models of cisplatin-induced cachexia, it has been shown that cisplatin treatment in fast-twitch skeletal muscle stimulated cell autophagy by decreasing the level of active Akt and therefore, phosphorylated FoxO3a, thus favoring its localization in the nucleus. Accordingly, a parallel upregulation of genes coding for autophagy proteins such as Beclin-1, a protein involved in autophagy starting, and LC3-II and p62 has also been observed [36]. A similar effect has been also associated to cisplatin in an in vitro study performed on C2C12 myotubes [37].…”
Section: Autophagy Pathwaymentioning
confidence: 78%
“…Indeed, levels of PGC-1α, NRF-1, and TFAM decreased in rats treated with cisplatin to an extent ranging from 30% to 50% compared to control animals. The change of PGC-1α might be due to the impairment of the PI3K-Akt-mTOR signaling pathway induced by cisplatin in this cachectic animal model [36]. Accordingly, changes in mtDNA levels were also observed [36].…”
Section: Mitochondrial Biogenesis and Dynamicmentioning
confidence: 83%
See 3 more Smart Citations